Angle of incidence effects on H2 dissociation and adsorption on defective Pt (111) surface: An an initio study - Natividad, Michelle T. (Animo Repository, 2009)
In this study, we determine the dependence of H2 adsorption on the incident angle by which H2 approaches the vacant site in a Pt surface. We calculate the potential energy for H2 dissociative adsorption on a defective P(111) surface as function of the H2 interatomic distance r and the H2 center of mass (CM) distance Z from the surface for different incident angels and approach sites. Potential energy plots as functions of the H2 CM distance Z from the surface reveal that H2 dissociative adsorption occurs for angels of incidence 15o and 30o for both the top site and FCC site as approach sites with one atom residing closer to the Pt surface than the other H atom. For the angel of incidence 0 = 55o, adsorption does not occur for H2 approaching the top site while it may occur but unstable for H2 approaching the FCC site. No activation barrier was observed for H2 approaching the top site at 0 = 15o. The highest adsorption energy is found to occur at 0 = 15o for both approach sites. The adsorption energy is found to decrease and may vanish as the incident angle is increased suggesting that H2 adsorption is more favorable at small incident angles.